Effects of beer advertisings on youth's intention towards alcohol consumption. - Yu, Angela Yah Kie. (2008)
The purpose of this paper is to study the effects of televised beer advertisements on youth's intention to drink as an adult. In previous media effect studies, media were found to shape the audience's worldview. The literature review examines several theories with regards to alcohol consumption, including the theory of brand capital, consumer demand theory, decision theory, subjective expected utility theory, the theory of reasoned action, social cognitive theory and theory of planned behaviour. A model is proposed, which the youths' intention towards alcohol consumption (which is mediated by four psychological factors - positive outcome expectancies, negative outcome expectancies, positive social effects and low self-efficacy of alcohol avoidance in the social cognitive theory) - is hypothesised to be influenced by exposure to beer advertising.